DIPLOMASI KEBUDAYAAN KOREAN CULTURAL CENTER INDONESIA PASCA PANDEMI COVID-19 TAHUN 2022–2025 - Andini Shima Warni; Christy Damayanti; Sritami Santi Hatmini (Solidaritas, 2025)
The COVID-19 pandemic significantly impacted cultural diplomacy activities, including those carried out by the Korean Cultural Center Indonesia (KCCI). This study aims to analyze the strategies and forms of cultural diplomacy implemented by KCCI in the post-pandemic period of 2022–2025. Using a descriptive qualitative approach and literature review techniques, data were obtained through documents, digital archives, and KCCI's official social media platforms. The results show that KCCI transitioned from a hybrid model to offline, while still leveraging digital media, collaboration with local communities, and educational institutions. The cultural diplomacy strategies included cultural exhibitions, Korean language competitions, digital cultural exchange, and public engagement via social media. Based on Nicholas J. Cull’s public diplomacy theory and Warsito & Kartikasari’s cultural diplomacy framework, KCCI successfully sustained South Korea’s soft power in Indonesia through adaptive and participatory program innovation. Keywords: cultural diplomacy, KCCI, South Korea, soft power, post-pandemic